I survived : the sinking of the Titanic, 1912 - Ball, Georgia (I survived (Graphic novel series), 2020)
A young boy named George Calder, who is sailing with his aunt and little sister on the "Titanic," tries to escape to a lifeboat when the ship strikes an iceberg. Includes additional facts, photographs, and information about the sinking of the "Titanic."